(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to investigate the effect of various concentrations of different growth regulators on the aspect of callus induction along with shoot regeneration and root formation of sweet potato viz. BARI 6. For callus induction, MS medium was used supplemented with different concentrations of 2,4D and Kinetin. Different concentrations of BAP were used for shoot regeneration. Different concentrations of NAA and a constant level of BAP were also used for root development. For callus characters, 2,4D at 0.5 mg L1 + kinetin at 0.5 mg L1 Treatments we the maximum callus induction (90.00%), highest weight of callus at 15 days (4.64 g) and 35 days (5.63 g) of culture while similar treatment requiring the minimum time (5.67 days) to callus initiation. Among the various concentrations of BAP, maximum shoot regeneration (81.67%), minimum time (7.33 days) for shoot initiation, maximum leaves shoot1 (11.92) and longest shoot (5.25 cm) were recorded in 2.50 mg L1 BAP while BAP at 2.0 mg L1 in combination with NAA at 1.0 mg L1 observed the maximum root formation (71.67%) and longest root (10.58 cm) with an average minimum time for root initiation (7.50 days) in the present study. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22117 J. Environ. Sci. & Natural Resources, 6(2): 197-200 2013